2020
DOI: 10.1088/1741-4326/ab7d50
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced helium exhaust during edge-localized mode suppression by resonant magnetic perturbations at DIII-D

Abstract: Effective helium confinement time, τ p * ,He , and its ratio with energy confinement time, τ p * ,He /τ E , are key metrics quantifying the suitability of fusion plasmas for a continuous burn. Comparisons in the DIII-D tokamak of discharges with suppression of edge localized modes (ELMs) by resonant magnetic field perturbations (RMPs) to the corresponding unperturbed ELMy discharges found that both of these metrics were strongly reduced, by a factor of approximately 2, after application of the RMPs. This reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…For comparison, τ p /τ e ≈ 1.5 for the ELMy discharge without RMPs. This is consistent with experiments that have shown that RMPs reduce the particle confinement time in discharges with He impurity injection [27]. To study the impurity density evolution in more detail and to understand if the Al 13+ charge state density is indicative of the total impurity density, the STRAHL transport code is used.…”
Section: Evolution Of the Al Density Profilesupporting
confidence: 78%
“…For comparison, τ p /τ e ≈ 1.5 for the ELMy discharge without RMPs. This is consistent with experiments that have shown that RMPs reduce the particle confinement time in discharges with He impurity injection [27]. To study the impurity density evolution in more detail and to understand if the Al 13+ charge state density is indicative of the total impurity density, the STRAHL transport code is used.…”
Section: Evolution Of the Al Density Profilesupporting
confidence: 78%
“…However, the decay time of the Ar 16 + after each pulse is clearly longer in comparison to the ELMy phase after 6.8 s suggesting an increased Ar core confinement time under ELM-suppressed conditions and/or a reduced pumping efficiency. Recent helium exhaust experiments comparing RMP ELM-suppressed and non-perturbed ELM H-modes in DIII-D showed a better global exhaust of helium with RMPs [34]. A caveat of the present scenario regarding radiative power exhaust is the low density required for ELM suppression [31], which reduces the radiated power per Ar ion in the core and divertor and also leads to slow pumping, challenging active control.…”
Section: Ar Injection Into Resonant Magnetic Perturbation (Rmp) Elm-s...mentioning
confidence: 85%
“…Impurity experiments using n = 3 RMP fields to suppress ELMs in ITER-shaped plasmas found a factor of 2-3 reduction in the effective helium particle confinement time compared to ELMy H-modes without RMP fields [53]. Measurements of neutral partial pressures in the pumping plenum from Penning gauges show the partial pressure of helium increases substantially more than that of deuterium during RMP ELM-suppression for a range of cases, in comparison with ELMy cases.…”
Section: Effect Of Rmp On Plasma Edgementioning
confidence: 95%
“…1 ITER Organization 2 General Atomics 3 Oak Ridge National Laboratory 4 National Institute for Fusion Science, Japan 5 Max-Planck Institute for Plasma Physics 6 Durham University 7 Lawrence Livermore National Laboratory 8 Princeton Plasma Physics Laboratory 9 University of Texas, Austin 24 Universita di Milano-Bicocca 25 Stony Brook University (SUNY) 26 University of Tennessee, Knoxville 27 Southwestern Institute of Physics, China 28 University of California, Irvine 29 University of Toronto 30 Auburn University 31 Palomar College 32 Kungliga Tekniska Hogskolan 33 Princeton University 34 Chambers University of Technology (Sweden) 35 Istituto di Fisica del Plasma CNR-EURATOM 36 United Kingdom Atomic Energy Authority (CCFE) 37 Oak Ridge Institute for Science Education 38 Aalto University 39 Korea National Fusion Research Center 40 Georgia Tech 41 Australian National University 42 Ulsan National Institute of Science and Technology 43 National Institutes for Quantum and Radiological Science, Japan 44 Harvard University 45 SLS2 Consulting 46 Far-Tech, Inc. 47 STI Optronics, Inc. 48 Tech-X Corporation 49 The College of William and Mary 50 General Atomics Temp 51 Qinzhou University 52 General Atomics (Retired) 53 University of Nice 54…”
Section: Affiliationsmentioning
confidence: 99%